Adaptasi Cerita Kakawin Arjuna Wiwaha pada Pewayangan Jawa Lakon Arjuna Wiwaha - Jiphie Gilia Indriyani; Kholidah Sunni Nafisah; Ainur Rosidah; Durotun Nashichah; Muhammad Fahrur Rozi; Evi Istiani; Shofihatul Millah; Yulike Aulia Familasari (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
Kakawin Arjunawiwaha is the first milestone of literature in East Java, in which there is a perfection of life as explained in other stories of wayang. Arjuna as the most handsome puppet play is an ideal illustration of Javanese culture about the image of a knight. This study aims to find out the story of Kakawin Arjuna Wiwaha in the Javanese puppet play of Arjuna Wiwaha. This study uses a qualitative research method based on a literature review of Kakawin Arjuna Wiwaha Wiryamartana (1987) which has been translated into Indonesian. The results of the study include: (1) Describing the story of Kakawin Arjuna Wiwaha in the Javanese puppet story Arjuna Wiwaha, (2) The characters in Kakawin Arjuna Wiwaha used in Javanese puppets of Kakawin Arjuna Wiwaha, (3) The response of the Javanese community towards Javanese puppets Arjuna Wiwaha adapted from the story of Kakawin Arjuna Wiwaha, especially on the characteristics of Arjuna as a person who is knighted, powerful and exemplary. Overall, it can be seen that there is a connection between the story of Kakawin Arjuna Wiwaha and the Javanese puppet play of Arjuna Wiwaha.